EPC and 4G packet networks driving the mobile broadband revolution - Olsson, Magnus (Academic Press, 2013)
Offers detailed insight into the Evolved Packet Core (EPC) that covers the standards and industry developments. This book describes and explains the entire EPC including architecture, features and protocols, giving you the knowledge and insight to see the potential in EPC, develop EPC products and deploy LTE/EPC mobile broadband Networks.